Observation of laser-assisted electron-impact ionization in ultrashort intense laser fields - Hiroi, Takashi; Morimoto, Yuya; Kanya, Reika; Yamanouchi, Kaoru (Physical Review A, 2021)
A laser-assisted (e, 2e) [LA(e, 2e)] process of Ar in an ultrashort (1.2 ps) near-infrared intense laser field, Ar + e(-) + h nu -> Ar+ + e(-) + e(-), was observed by coincidence measurements of the fast electron scattered forward within the small-angle range and the slow electron emitted to the wide-angle range. The spectrum of the sum of the kinetic energies of fast and slow electrons exhibited a shoulder structure at the one-photon energy shift from the (e, 2e) peak for the Ar 3p orbital, which was unambiguously assigned to the LA(e, 2e) process with the one-photon energy gain. The determined triply differential cross section of the LA(e, 2e) process with one-photon gain from the laser field was approximately twice as large as a theoretical estimate and this enhancement was regarded as an evidence of the formation of light-dressed states of Ar.
CRIS-Team WoS Importer:2022-01-07